2015
DOI: 10.1371/journal.pone.0132788
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Disorders in the Emergency Department: Independent Risk Factors for Mortality

Abstract: BackgroundCalcium disorders are common in both intensive care units and in patients with chronic kidney disease and are associated with increased morbidity and mortality. It is unknown whether calcium abnormalities in unselected emergency department admissions have an impact on in-hospital mortality.MethodsThis cross-sectional analysis included all admissions to the Emergency Department at the Inselspital Bern, Switzerland from 2010 to 2011. For hyper- and hypocalcaemic patients with a Mann-Whitney U-test, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…One national report in the UK stated that in-hospital AKI could have been avoided in one-fifth of the patients if they had received better monitoring of electrolytes, recognition of risk factors, and prompt management [37]. In our study, EAD was associated with a 2.0-fold increase in the hazard ratio of in-hospital death, as well as longer length of stay and higher hospital costs, consistent with other studies [38][39][40]. The median survival time sustained declining along with the rise of EAD number and severity.…”
Section: Discussionsupporting
confidence: 89%
“…One national report in the UK stated that in-hospital AKI could have been avoided in one-fifth of the patients if they had received better monitoring of electrolytes, recognition of risk factors, and prompt management [37]. In our study, EAD was associated with a 2.0-fold increase in the hazard ratio of in-hospital death, as well as longer length of stay and higher hospital costs, consistent with other studies [38][39][40]. The median survival time sustained declining along with the rise of EAD number and severity.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, it seems obvious that hypocalcemia will affect cardiac contractility, and this was proved in current studies (3). Meanwhile, recent evidence suggests that vitamin D and parathormone (PTH) may have an independent role to play, also (4,5).…”
Section: Introductionmentioning
confidence: 62%
“…Reports have found conflicting results with either no association of calcium levels with mortality or both high and low levels of Ca reported to be associated with an increase in mortality ( 1 , 2 , 3 , 4 , 29 ). Sauter et al studied unselected patients admitted to the ED and found that both hypocalcemia and hypercalcemia were associated with increased 28-day in-hospital mortality ( 1 ). Egi et al found similar results in patients admitted to ICU ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…There has been growing interest in hypocalcemia as an independent risk factor for mortality among patients admitted to the emergency department (ED) and ICUs ( 1 , 2 , 3 , 4 ). Recently, hypocalcemia has been associated with the risk of sudden cardiac arrest (SCA) in the community ( 5 ).…”
Section: Introductionmentioning
confidence: 99%